Effects of selenium supplementation on concurrent chemoradiotherapy in patients with cervical cancer: A randomized, double-blind, placebo-parallel controlled phase II clinical trial - Yang, Mei; Pei, Bo; Hu, Qiancheng; Li, Xiaoying; Fang, Xiping; Huang, Xue; Yang, Zunjing; Chen, Jiaquan; He, Du; Sun, Guogen; Lv, Peng; Wang, Li; et al. (Frontiers in Nutrition, 2023)
Objective: Selenium (Se) is an essential trace element and may be able to affect cervical cancer occurrence and progression. The aim of this study was to determine the safety profile of add-on Se yeast, and assess the potential of Se to ameliorate hematologic toxicity of concurrent chemoradiotherapy in patients with cervical cancer. Methods: Patients with stage IIB cervical cancer who met all inclusion criteria were randomly assigned to either the experimental group or the control group.The experimental group received Se yeast tablets (100µg Se, twice daily) while the control group received placebos (twice daily) for 5 weeks in total. All patients of both groups received standard treatment including: pelvic external irradiation, concurrent five cycles of chemotherapy, and brachytherapy. Measures included the incidence of myelosuppression, impairment of liver and kidney function, objective response rate, as well as blood Se concentrations before, during and after the treatment of the two groups. Results: 104 eligible patients were enrolled to the experimental group (n=50) or the control group (n=54). Objective Response Rates (ORR) in the experimental group and control group were 96% and 94%, respectively (P=0.47). The baseline levels of blood Se before treatment in the experiment and control groups were similar (58.34±17.63 µg/L and 60.21±18.42 µg/L, P=0.60), but the concentrations became significantly different after the course completion between the two groups (76.16 ± 24.47 µg/L and 57.48 ±14.92 µg/L separately, P<0.01). Se dramatically decreased the incidence of grade 3 myelosuppression (48% vs 63%, P=0.034) compared to the control group. In the subgroup of patients with moderately-well differentiated cervical cancer, the incidence of thrombocytopenia induced by concurrent chemoradiotherapy was lower in the experimental group than in the control group (53.8% vs 78.9%, P<0.01). However, no difference was observed in the liver and kidney injuries between the two groups. Conclusion: Supplementation of Se effectively increased blood Se levels in Se-inadequate cervical cancer patients. As an add-on to standard treatment, Se-yeast significantly decreased the hematologic toxicity of concurrent chemoradiotherapy.